Norwegian by night [compact disc, unabridged] : a novel - Miller, Derek B., 1970- (Bolinda Audio ; Distributed by Brilliance Audio, 2013)
Sheldon, 82 years old, impatient, and unreasonable and is staying with his granddaughter's family in Norway when he disappears with a stranger's child. Sheldon is an ex-Marine, and he feels guilty for his son's death in Vietnam. To Norway's cops, Sheldon is just an old man who is coming undone from a long and hard life. But Sheldon is clear in his own mind. He'd heard the boy's eastern European mother being murdered, and he's determined to protect the child from the killer and his Balkan gang.